2009
DOI: 10.3184/146867809x466221
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Oxidation of Dl-Methionine by Benzimidazolium Dichromate

Abstract: The oxidation of DL-methionine (MT) by benzimidazolium dichromate (BIDC), in dimethyl sulfoxide, leads to the formation of the corresponding sulfoxide. The reaction is first order with respect to BIDC. Michaelis - Menten type kinetics were observed with respect to MT. The reaction is catalysed by hydrogen ions and the dependence is of the form kobs = k‘[H+]. The rate of oxidation of MT was determined in 19 organic solvents. An analysis of the solvent effect by solvatochromic equations indicated that though bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…No effect of added benzimidazolium ion on the rate of oxidation also supports the postulation that BIDC remain as nonionised. 5 The crystal structure study of BIDC, reported by Meng et al 15 supports the non-ionic nature of the oxidant in the reaction system. The dichromate ion connects two benzimidazolium rings via.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…No effect of added benzimidazolium ion on the rate of oxidation also supports the postulation that BIDC remain as nonionised. 5 The crystal structure study of BIDC, reported by Meng et al 15 supports the non-ionic nature of the oxidant in the reaction system. The dichromate ion connects two benzimidazolium rings via.…”
Section: Discussionmentioning
confidence: 96%
“…The dependence of k obs on the concentration of aldehyde was studied at different temperatures and the values of K and k 2 were evaluated from the double reciprocal plots using equation (5). The thermodynamic parameters for the complex formation and the activation parameters for the decomposition of complexes were calculated from the values of K and k 2 respectively, at different temperatures (Tables 3 and 4).…”
Section: Rate Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been interested in the kinetics and mechanism of the oxidation by newer complexes of Cr(VI). We have published a few reports on the kinetic www.prkm.co.uk and mechanistic aspects of the oxidation by BIDC [3][4][5][6][7][8][9][10]. In continuation of our earlier studies, we report here the kinetics and mechanism of the oxidation of mandelic acid (MA) and nine monosubstituted MAs by BIDC in dimethyl sulfoxide (DMSO), a non-aqueous solvent.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 a two electron transfer mechanism leading to the formation of Cr(IV) intermediate; 16 the mechanism involving the formation of a chromate thioester 17 and its disproportionation in a slow step; 18 the S N 2 mechanism involving a nucleophilic attack of sulfur on chromium followed by ligand coupling between S and O; 15,19,20 the mechanism which follows Michalies-Menten kinetics with complex formation 21 and slow decomposition of the complex. 22 The present study of oxidative decarboxylation of phenylsulfinylacetic acid (PSAA) by Cr(VI) will be of particular interest owing to the application of PSAA in pharmaceutical preparations and in the synthesis of several organic compounds.…”
Section: Introductionmentioning
confidence: 99%